Between sovereignty and globalisation : where does the United Nations fit in? - Urquhart, Brian (2000)
Argues that globalization is no panacea for worldwide development and may in fact be of more limited benefit than was first recognised. Points to a number of areas where it has raised more questions than it has provided answers. Argues also that the United Nations should not be considered passé when these issues are debated, but that the organisation can and should play a much larger role than it is doing right now.